2002
DOI: 10.1007/s00239-002-2347-8
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic-Type Ribonuclease 1 Gene Duplications in Rat Species

Abstract: Mammalian pancreatic-type ribonucleases (RNases) 1 represent single-copy genes in the genome of most investigated mammalian species, including Mus musculus and other murid rodents. However, in six species belonging to the genus Rattus and closely related taxa, several paralogous gene products were identified by Southern blotting and PCR amplifications of genomic sequences. Phylogenies of nucleotide and derived amino acid sequences were reconstructed by several procedures, with three Mus species as outgroup. Du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…; Atchison and Adesnik 1986;Pages et al 1990;Yan et al 1995;McFadyen et al 1999;Ioannidu et al 2001;Oldfield et al 2001;Rolstad et al 2001) were validated during our analysis, not all were detected. For example, the pancreatic type ribonuclease I represents a single-copy gene within most mammalian lineages that has expanded specifically within the genus Rattus (Dubois et al 2002). It was not detected as a duplicated gene within rat genome assembly v. 3.1 by our criteria.…”
Section: Genome Research 501mentioning
confidence: 85%
“…; Atchison and Adesnik 1986;Pages et al 1990;Yan et al 1995;McFadyen et al 1999;Ioannidu et al 2001;Oldfield et al 2001;Rolstad et al 2001) were validated during our analysis, not all were detected. For example, the pancreatic type ribonuclease I represents a single-copy gene within most mammalian lineages that has expanded specifically within the genus Rattus (Dubois et al 2002). It was not detected as a duplicated gene within rat genome assembly v. 3.1 by our criteria.…”
Section: Genome Research 501mentioning
confidence: 85%
“…However, the study of the adaptive evolution of RNASE superfamily in rats and mice found that a group of eight genes in this superfamily in rat is evolving under positive selection, suggesting that numerous gene duplications and functional diversification events have occurred at these loci [60]. Subsequently, Dubois et al [26] investigated pancreatic RNASE1 gene of Rattus species and several their sister taxa. Surprisingly, they observed a "birth (gene duplication)-and-death (gene deactivation)" process for the evolution of pancreatic RNASE1 genes in R. norvegicus, while other species had only one RNASE1 gene [1].…”
Section: Other Physiological Functions Of Rnase1 Genementioning
confidence: 99%
“…Surprisingly, they observed a "birth (gene duplication)-and-death (gene deactivation)" process for the evolution of pancreatic RNASE1 genes in R. norvegicus, while other species had only one RNASE1 gene [1]. In addition, the duplicated genes were found to undergo rapid evolution [26,61]. Isolation and purification of proteins further suggest that one of these genes is expressed with a high level in pancreas, while the other genes are expressed in other tissues [26].…”
Section: Other Physiological Functions Of Rnase1 Genementioning
confidence: 99%
See 2 more Smart Citations